65.8k views
5 votes
Given that f(x) = 2x + 1 and g(x) = -5x + 2, find f(g(3)).

User JohnFx
by
5.1k points

2 Answers

7 votes


\bf \begin{cases} f(x) = 2x + 1\\ g(x) = -5x+2 \end{cases} \\\\[-0.35em] ~\dotfill\\\\ g(3) =-5(3)+2\implies g(3) = -15 + 2\implies \boxed{g(3) = -13} \\\\\\ f(~~g(3)~~)\implies f\left( \boxed{-13} \right)=2(-13)+1\implies \stackrel{f(~g(3)~)}{f(-13)}=-25

User Sahil Dhankhar
by
5.8k points
5 votes

Answer:

f(g(3))=-25

Explanation:

f(x) = 2x + 1

g(x) = -5x + 2

we have:

f(g(x))=2(-5x + 2) + 1

f(g(3))=2(-5(3) + 2) + 1

f(g(3))=2(-15 + 2) + 1

f(g(3))=2(-13) + 1

f(g(3))=2(-13) + 1

f(g(3))=-26+1

f(g(3))=-25

User Arief Hidayat
by
5.4k points